Descriptive analysis of sustainable manufacturing indicators in Malaysian manufacturing firms - Nordin, Norani; Adebambo, Hameed O. (UMP Publisher, 2016)
Manufacturing companies have been forced to give considerations to sustainable manufacturing practices due to the alarming social and economic factors. However, very few studies have investigated the extent of sustainable manufacturing practices within the context of developing countries, particularly in Malaysia. This study seeks to explore the extent of sustainable manufacturing implementation among Malaysian manufacturing firms. One hundred and four usable questionnaires were collected and analysed by using SPSS version 20. The findings revealed that among the three dimensions of sustainable manufacturing, the social well-being and economic have shown to be practiced to a large extent by Malaysian manufacturing firms. However, the lowest sustainable manufacturing practices implemented dimension is environmental. More efforts are needed to ensure that the Malaysian manufacturing firms consider the sustainable manufacturing practices more seriously. This study suggests that the scenario of sustainable manufacturing in Malaysia is yet to be strategic. Hence, more efforts are needed to ensure that the Malaysian manufacturing firms consider the sustainable manufacturing practices as a strategic measure to enhance performances